Practical health co-operation-the impact of a referral template on quality of care and health care co-operation: study protocol for a cluster randomized controlled trial - Wåhlberg, Henrik; Valle, Per Christian; Malm, Siri; Broderstad, Ann Ragnhild (Trials, 2013)
Background: The referral letter plays a key role both in the communication between primary and secondary care, and in the quality of the health care process. Many studies have attempted to evaluate and improve the quality of these referral letters, but few have assessed the impact of their quality on the health care delivered to each patient. Methods: A cluster randomized trial, with the general practitioner office as the unit of randomization, has been designed to evaluate the effect of a referral intervention on the quality of health care delivered. Referral templates have been developed covering four diagnostic groups: dyspepsia, suspected colonic malignancy, chest pain, and chronic obstructive pulmonary disease. Of the 14 general practitioner offices primarily served by University Hospital of North Norway Harstad, seven were randomized to the intervention group. The primary outcome is a collated quality indicator score developed for each diagnostic group. Secondary outcomes include: quality of the referral, health process outcome such as waiting times, and adequacy of prioritization. In addition, information on patient satisfaction will be collected using self-report questionnaires. Outcome data will be collected on the individual level and analyzed by random effects linear regression. Discussion: Poor communication between primary and secondary care can lead to inappropriate investigations and erroneous prioritization. This study’s primary hypothesis is that the use of a referral template in this communication will lead to a measurable increase in the quality of health care delivered.